2004
DOI: 10.1111/j.1523-1755.2004.00399.x
|View full text |Cite
|
Sign up to set email alerts
|

The uremic solutes p-cresol and indoxyl sulfate inhibit endothelial proliferation and wound repair

Abstract: We demonstrated that both p-cresol and indoxyl sulfate decrease endothelial proliferation and wound repair. These solutes could play a role in endothelial dysfunction observed in uremic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
332
2
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 429 publications
(344 citation statements)
references
References 44 publications
8
332
2
2
Order By: Relevance
“…[4] Recent studies have suggested that indoxyl sulfate may also be involved in the mechanisms underlying the progression of atherosclerotic lesions in CKD patients. Dou et al [6] found that two uremic toxins, indoxyl sulfate and p-cresol, inhibited endothelial proliferation and decreased endothelial wound repair, and concluded that indoxyl sulfate and p-cresol may play a role in endothelial dysfunction in uremic patients. Bammens et al [14] reported that free serum concentrations of the protein-bound retention solute pcresol predict mortality in hemodialysis patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4] Recent studies have suggested that indoxyl sulfate may also be involved in the mechanisms underlying the progression of atherosclerotic lesions in CKD patients. Dou et al [6] found that two uremic toxins, indoxyl sulfate and p-cresol, inhibited endothelial proliferation and decreased endothelial wound repair, and concluded that indoxyl sulfate and p-cresol may play a role in endothelial dysfunction in uremic patients. Bammens et al [14] reported that free serum concentrations of the protein-bound retention solute pcresol predict mortality in hemodialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…[5] Recent studies have suggested that increased serum levels of indoxyl sulfate and p-cresol in CKD patients may contribute to not only kidney damage but also to vascular lesions, including atherosclerotic lesions, which are closely related to cardiovascular events frequently observed in dialysis patients. [6,7] Cardiovascular diseases are the leading cause of mortality in CKD patients. [8] The above observations raise a possibility that reduction of circulating uremic toxins by AST-120 prior to the initiation of dialysis in CKD patients may improve their prognosis even after the initiation of dialysis.…”
Section: Introductionmentioning
confidence: 99%
“…However, some in vitro studies have revealed the toxicity of IS in vascular cells. 14,33,34 In addition, oxidative stress induced by IS may damage vascular cells in an indirect manner. 26,27,36 Therefore, IS accumulation is considered to be one of the pathogenic mechanisms causing endothelial dysfunction in patients with CKD.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 IS inhibited endothelial proliferation and wound repair, and increased endothelial microparticles in human umbilical vein endothelial cells (HUVEC). In this study, we showed that the endothelium-dependent aortic response correlated significantly with serum IS levels.…”
Section: Discussionmentioning
confidence: 99%
“…The reduced excretion of indoxyl sulfate in urine may indicate an elevated level in the serum of endothelial dysfunction rats. In an in vitro study, indoxyl sulfate induced endothelial dysfunction by inhibiting endothelial proliferation and migration [22]. It has been suggested that indoxyl sulfate also plays a role in oxidative stress by increasing NAD(P)H oxidase activity in endothelial cells and the production of reactive oxygen species (ROS), and by strongly decreasing the level of glutathione, one of the most active antioxidant systems in cells [23,24].…”
Section: Metabonomic Fingerprint Analysis Of Endothelial Dysfunctionmentioning
confidence: 99%